2015
DOI: 10.1089/gtmb.2014.0251
|View full text |Cite
|
Sign up to set email alerts
|

Screening for AZFc Partial Deletions in Dravidian Men with Nonobstructive Azoospermia and Oligozoospermia

Abstract: Context: Dravidians are the predominant population residing in South India with a diverse genetic structure. Considering various genetic discoveries taking place today, it is evident that deletions in the AZFc region are the most common cause of severe spermatogenic failure (SSF) in various populations studied. However, it is significant to note that there is a paucity of scientific literature on AZFc subdeletion screening among the Dravidian population. Objective: To investigate the prevalence and association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
1
11
3
1
Order By: Relevance
“…Obtaining 4.72% rate of azoospermia factor, microdeletions of the Y chromosome in severe oligozoospermic men and azoospermic infertile men support this hypothesis that AZFa, b, d and c sub‐regions of the Y chromosome are critical for spermatogenesis. Although this estimation was lower than the previously reported data, this deduction was mentioned in other studies (Ambulkar et al., ; Omrani, Samadzadae, Bagheri, & Attar, ; Totonchi et al., ; Vijesh, Nambiar, Mohammed, Sukumaran, & Suganthi, ; Zaimy et al., ). Testicular sperm extraction (TESE) is not advisable on azoospermic carriers of AZFa, AZFabc, AZFbc and AZFb microdeletions.…”
Section: Discussioncontrasting
confidence: 65%
“…Obtaining 4.72% rate of azoospermia factor, microdeletions of the Y chromosome in severe oligozoospermic men and azoospermic infertile men support this hypothesis that AZFa, b, d and c sub‐regions of the Y chromosome are critical for spermatogenesis. Although this estimation was lower than the previously reported data, this deduction was mentioned in other studies (Ambulkar et al., ; Omrani, Samadzadae, Bagheri, & Attar, ; Totonchi et al., ; Vijesh, Nambiar, Mohammed, Sukumaran, & Suganthi, ; Zaimy et al., ). Testicular sperm extraction (TESE) is not advisable on azoospermic carriers of AZFa, AZFabc, AZFbc and AZFb microdeletions.…”
Section: Discussioncontrasting
confidence: 65%
“…The involvement of b1/b3 is yet controversial. In the present study and that reported recently [35], b1/b3 deletions were not found to be associated with male infertility; however, Shahid et al [34] found a significantly higher numbers of infertile subjects with b1/b3 deletions. At present, the reason for such discrepant findings is unknown; to rule out an effect of sample numbers, we pooled the data from all the three studies and analysed the data statistically.…”
Section: Discussioncontrasting
confidence: 56%
“…To strengthen the statistical analysis we pooled the data derived from this study and also reported earlier in the Indian population [34,35]. The results revealed that the gr/ gr deletions were significantly higher in azoospermic and oligozoospermic men.…”
Section: Frequency Of Azfc Subdeletionsmentioning
confidence: 71%
See 1 more Smart Citation
“…This was higher than previously reported in Germany (1%) (20) , South Iran (1.25%) (21) , and India (0.97%) (22) . However; This prevalencewas Ashraf A. Abd El-Latif.et al 132 less than previous studies on Egyptian azoospermic men; 5% (16) , and 9.2% (18) ; and also patients from other countries; 7.4 in a Han-Chinese population (23) , and 9.17% in Dravidian-Indian (24) .…”
Section: Discussionmentioning
confidence: 68%